PENGARUH PERDAGANGAN INTERNASIONAL, NILAI TUKAR, INFLASI, DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI NEGARA BRICS - Jesslyn Thesia; Wahyu Ario Pratomo; M.Syafii (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effects of international trade, exchange rates, inflation, and investment on economic growth in BRICS countries using indicators such as the ratio of exports of goods and services to GDP, exchange rates against the US dollar, consumer price index, gross fixed capital formation (GFCF) to GDP ratio, and Gross Domestic Product (GDP). The analytical method employed is the Panel Autoregressive Distributed Lag (ARDL) model, using EViews 12 software. The data used in this study are panel data, combining cross-sectional data from BRICS countries (including Indonesia) and time series data from 2015 to 2024 sourced from the World Bank.The results indicate that in the short run, exchange rates have a negative and significant effect on economic growth, while international trade, investment, and inflation do not have a significant effect. In the long run, all variables—international trade, exchange rates, inflation, and investment—have a positive and significant effect on economic growth in BRICS countries.